‘Jengking’ the Champs in Shell Eco-Marathon Asia 2012 - UMP, PNC
A group of undergraduates who were members of the SAE-UMP Club Universiti Malaysia Pahang (UMP) Chapter did the university proud when the car they invented called ‘Jengking’ (Scorpion) was announced as the winner in the Urban Diesel category at the Shell Eco- Marathon Asia 2012.